Remembering survival inside a Nazi slave-labor camp - Browning, Christopher R. 1944- (Norton, 2011)
Draws on the testimony of survivors of the Holocaust-era Starachowice slave-labor camps to examine the Jewish prisoners' fight for survival through a succession of brutal Nazi camp regimes